Analisis Pertanggungjawaban Tenaga Medis yang melakukan Tindak Pidana Malpraktek menurut UU Nomor 36 Tahun 2009 Tentang Kesehatan - Suwari Akhmaddhian (UNIFIKASI : Jurnal Ilmu Hukum, 2014)
A defense against criminal liability of a health worker who commit criminal acts of malpractice can be argued that the criminal liability lies in the form of omission errors or omissions when power kesehatantersebut their profession . As a result of mistakes resulting in death or injury , an element of health personnel mistakes made in this case is the gross negligence or culpa lata which will be requested a defense response of the consequences of his actions . In the application of the criminal law against the perpetrators of malpractice , the application of positive law for perpetrators of malpractice contained in Article 361 and Article 359 of the Code of Criminal Law and Law no . 36 of 2009 on Health . But in the application of these articles dilemma arises in understanding the elements of negligence which measures whether the health worker negligence or not in terms of their profession , to the order of the Book  of the  Law is  being revised  Criminal Law should  regulate the issue of negligence is regulated in detail and.clear.Keywords : Health , Criminal , Malpractice.